Individual, interpersonal, and contextual factors associated with discrepancies between intended and actual spring break drinking. (June 2017) - Lee, Christine M.; Patrick, Megan E.; Geisner, Irene Markman; Mastroleo, Nadine R.; Mittmann, Angela; Zimmerman, Lindsey
Abstract: The purpose of the present paper was to examine the extent to which college students underestimate the quantity of alcohol they will consume during Spring Break (SB), and whether individual, interpersonal, and contextual factors may be related to underestimation of SB drinking and drinking consequences. College students participated in web-based surveys prior to and after SB (N = 603; 57% women). Overall, results indicated that individual factors (being male, being a member of a fraternity or sorority, previously experiencing more alcohol-related consequences, and intending to drink less during SB), interpersonal factors (reporting friends encourage getting drunk), and contextual factors (going on a SB trip with friends and receiving drinks from others) predicted underestimating peak drinks consumed during SB. Underestimating the peak number of drinks to be consumed on SB was associated with experiencing a greater number of alcohol-related consequences. Targeted interventions designed specifically to focus on underestimation of college student drinking and the impact of SB contextual and interpersonal factors may be an important area of study to reduce negative consequences of alcohol use during SB. Highlights: Many college students underestimated how much they would drink during Spring Break. Individual factors (e.g., being male) predicted underestimating actual drinking. SB trips & having drinking pacts with friends predicted underestimating actual drinking. Receiving drinks from others predicted alcohol-related negative consequences. Students who underestimated their peak drinks on SB had more negative consequences.